The Relationship between Communication Behavior and Agricultural Extension Facilities Equipment in the Digital Era in South Bangka Regency - Yulia; Eddy Jajang Jaya Atmaja; Monica Kharisma Swandhi (Postgraduate, University of Mataram, 2025)
Connection behavior communication extension worker with equipment facility extension worker agriculture used extension worker in give related information with behavior communication very important for extension workers in operate task and its function. However, until moment This fulfillment need the For extension worker agriculture with behavior communication in search Not yet have optimal relationship for implemented. This study aims to analyze the relationship between the communication behavior of extension workers and the equipment of extension facilities in South Bangka Regency, Bangka Belitung Islands Province. The method used in study This is method descriptive quantitative with test correlation Spearman's Rank Results field research show that the relationship between the variables of extension facility equipment and the communication behavior of extension workers is positively correlated. Extension teaching aids are positively correlated with both local and cosmopolitan communication behavior. Likewise, extension aids are positively correlated with both local and cosmopolitan communication behavior.